Consumer-based approach to customer engagement - the case of luxury brands - Prentice, C.; Loureiro, S. M. C. (Journal of Retailing and Consumer Services, 2018)
The current study investigates a customer-based approach to customer engagement with a focus on behavioral engagement manifestations. Utilizing theories of social motives and positive psychology, the study proposes that desire and social value are related to consumers to engage with luxury fashion brands, and that such engagement leads to subjective well-being. The data was collected at a well-known venue for luxury fashion brands in Lisbon. The results show that social motives are indeed significantly related to customer engagement which affects an individual's subjective well-being. Some customer engagement behaviors partially mediate the relationship between social motives and well-being. Discussion of these findings and implications for the literature and practitioners conclude the paper.